INCREASED TENSILE STRENGTH OF DISSIMILAR FRICTION WELD JOINT OF ROUND BAR A6061/S15C USING UPSET FORCE AND ONE-SIDE CHAMFER ANGLE - Yudy Surya Irawan; Dwi Prasetyo; Teguh Dwi Widodo; Wahyono Suprapto; Tjuk Oerbandono (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2019)
An effort to increase the tensile strength of dissimilar friction weld joint of round bar A6061/S15C was done in this study using upset force and one-side chamfer angle. Commercial round bar aluminum alloy A6061 and carbon steel S15C were used as rotated and a stationary part, respectively in continuous drive friction welding (CDFW) process. Upset force variations of 10.5, 14, and 17.5 kN were used. CDFW process used burn of length of 15 mm for all CDFW specimens. Chamfer angle was machined on friction area of the S15C stationary part with the variation of 0 (without chamfer angle), 30 and 45 degrees. Tensile strength test, macrostructure observation and micro Vickers hardness testing, SEM-EDX analysis were performed. It was found that the smaller chamfer angle (30 degrees) produced maximum tensile strength of A6061/S15C CDFW joint. It occurred due to smaller formed flash, the lower temperature of the flash that indicate lower heat input and caused smaller heat affected zone and higher hardness in the CDFW joint. The higher upset force also yields higher tensile strength of CDFW joint due to the higher degree of plastic deformation during the upset stage of CDFW joint and this state contributes to higher hardness and tensile strength of A6061/S15C CDFW joint. SEM-EDX analysis result also confirmed that more aluminum existed on the fracture surface of the A6061/S15C CDFW specimen with maximum tensile strength.